Ultra-fast high temperature sintering (UHS) of Li1.5Al0.5Ge1.5P3O12 electrolyte: A rationalization of the heating schedule. Issue 5 (1st March 2022) - Wu, Jinghua; Lin, Yong; Kermani, Milad; Hu, Chunfeng; Grasso, Salvatore
Abstract: The renewed interest on Fast Firing has been motivated by the suppressed Li, Na volatilization during the short sintering cycle (a few seconds). Ultra-fast high temperature sintering represents the latest development in Fast Firing with heating rates approaching 10 4 °C/min. At present, there is no clear indication on how heating rate should be modulated to target a certain physical property. In this work, we compared different heating schedules to consolidate Li1.5 Al0.5 Ge1.5 P3 O12 electrolyte. Ultra-fast high temperature sintering carried under a single step current mode promoted the formation of radial cracks around the edge of the sample as a result of the differential shrinkage resulting from the inward heat fluxes. Multistep processing, based on the hybrid combination of conventional sintering (pre-sintering step) followed by UHS resulted in crack free samples. Under a discharge time as short as 160 s, hybrid UHS resulted in a relative density as high as 94.62% and conductivity of 1.72 × 10 −4 S/cm, surpassing conventional sintered counterparts.